Recuperação de depósitos de estéril em mina de fosfato com aplicação de Topsoil - Cardoso, Bruno Rocha (2020)
The recovery of the waste deposits generated during mining activities is recommended to help stabilize the geotechnical conditions of these structures and avoid environmental impacts, such as the transport of fine solids to streams and emission of particulate matter into the atmosphere. Some recovery practices common to these structures are hydroseeding, no-till, and topsoil application on the slopes of the deposits. Since topsoil is an organic material, rich in seeds and commonly generated in mining where there is native vegetation, its use for recovering areas impacted by mining has represented a good cost-benefit. Mosaic Fertilizantes of the Catalão-GO unit has successfully applied this technique for years and has inspired this paper. The objective was to evaluate the efficiency of topsoil transposition in a chronosequence of 15, 10, 5, and 1 year from the application. To determine the efficiency of the application, four quadrants of 300 m2 were outlined, identifying, characterizing, and qualifying all specimens of flora present in these areas. The species sampled and observed were classified according to their origin (native or exotic) and form of life (grass/liana, shrub/sub-shrub, and tree). The number of species sampled in each transect (without rarefaction) represented the richness since the sampling effort was the same in all four quadrants. The results indicated an increase in richness and plant cover and height in areas of different ages of topsoil transposition, over time, as was observed by Rodrigues et al. (2004). However, the frequency of botanical families such as Fabaceae and Poaceae drew attention, and the most dominant species in all plots were Cenchrus purpureus, followed by Urochloa decumbens (both agricultural cultivars of exotic herbaceous species), Piper arboretum, and Mucuna pruriens (both native shrubs), suggesting the persistence of exotic grass species. The study also indicated that the origin of the topsoil was predominantly from pasture areas and that there is a possibility that the evaluated areas are receiving diaspores from the remaining native vegetation, close to where the transposition took place. Finally, the study showed that the use of topsoil to recover slopes from the waste dump was efficient for maintaining its geotechnical characteristics, reducing particulate emissions, and restoring ecological functions, especially in regions where forest fragments contribute to the spread of propagules.